The Socioeconomic Impacts of COVID-19 on Households in Cambodia, Report No. 4 : Results from the High-Frequency Phone Survey of Households Round 4 (17 December 2020-12 January 2021) - Karamba, Wendy; Salcher, Isabelle; Tong, Kimsun (World Bank, Washington, DC, 2021)
The coronavirus disease 2019 (COVID-19) pandemic and its effects on households create an urgent need for timely data and evidence to help monitor and mitigate the social and economic impacts of the crisis on the Cambodian people, especially the poor and most vulnerable. To monitor the evolving socioeconomic impacts of the COVID-19 pandemic and inform policy responses and interventions, the World Bank designed and conducted a nationally representative High-Frequency Phone Survey (HFPS) of households in Cambodia. The survey covers important and relevant topics, including knowledge of COVID-19 and adoption of preventative behaviors, economic activity and income sources, access to basic goods and services, exposure to shocks and coping mechanisms, and access to social assistance. The survey will track the same households over 10 months, with selected respondents—typically the household head—completing interviews every 8 weeks. Monitoring the well-being of households over time will improve understanding of the effects of, and household responses to the COVID-19 pandemic in near-real time. This brief summarizes the findings of Round 4 (R4) of the HFPS. The information presented is based on a sample of 1,687 households, of which 410 were drawn from the nationally representative Living Standards Measurement Study Plus (LSMS+) survey and 1,277 from the list of beneficiaries of the conditional cash transfer program for pregnant women and children under 2 with an IDPoor equity card (IDPoor sample). IDPoor is Cambodia’s national poverty identification program and official targeting mechanism for programs that support the poor. Unless otherwise noted, the results presented are primarily drawn from the LSMS+ sample. To trace the evolution of key indicators, the results of Round 4 (R4) implemented in December 2020–January 2021 are compared against results of Round 3 (R3) implemented October–November 2020, Round 2 (R2) implemented August–September 2020, and Round 1 (R1) implemented May–June 2020.